Analisis Penerapan Keselamatan dan Kesehatan Kerja (K3) Menggunakan Metode Job Safety Analysis (JSA) pada PT. Adhi Persada Beton Batching Plant Kebonarum - Frysilia Tri Oktiasari; Ayudyah Eka Apsari (Journal of Student Research, 2025)
This study aims to analyze the implementation of occupational safety and health (OHS) and identify potential hazards and risks of work accidents in the production section of PT. Adhi Persada Beton Batching Plant Kebonarum using the Job Safety Analysis (JSA) method. The study was conducted with a descriptive analytical approach through direct observation. The results of the study showed that the highest risk of accidents occurred in the mobilization of the loader to the hopper, while moderate risks were found in the process of washing the mixer truck, loading concrete, transporting concrete to the casting location, and unloading concrete. The risk controls implemented, such as providing personal protective equipment (PPE), installing safety signs, and routine training, succeeded in reducing the risk level significantly.